Implementation of a Case Presentation Program for Clinical Nutrition Students - Shahbazi, Shaahin; Vahdat Shariatpanahi, Maryam; Vahdatshariatpanahi, Saba; Shahbazi, Erfan; Vahdat Shariatpanahi, Zahra (Frontiers in Nutrition, 2022)
Background and Aims: To implement a training method to increase clinical nutritionists’ knowledge and make doctors more familiar with this specialty. Methods: The study was conducted in an internship course of all third semester clinical nutrition students. At first, conventional training was presented for students, and then, in the same duration, case presentation training program was implemented. The presentations were filmed and uploaded to the internet, and the link was placed on the hospital's website. At the end of the 2 phases, the students were asked to answer the survey questionnaire. Additionally, consultation report sheets were evaluated and scored by 2 physicians. Number of consultation requests was also recorded in 2 study phases. Results: The mean satisfaction score was statistically higher in the case presentation training program than in the conventional program. All the students recommended similar case report program courses for the students in the future. Although the mean consultation report score was not statistically different between the two training programs, case presentation program resulted in significantly better scores in 4 items of nutrition focused physical examinations, assessment of malnutrition, assessment of related laboratory tests, and food-drug interactions. Number of consultation requests was significantly increased during the case presentation program training compared to the conventional training from 194 to 272 (P<0.001). Conclusion: From the students’ perspective, the case-based learning report was preferred to the conventional method. From the physicians' viewpoint, the answer to the counseling sheets was more complete and helpful.